Analisis Struktur Modal PT. Bakrie & Brother, Tbk Periode 2005 - 2008 - , Ruly Pahlevi ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Bakrie & Brotherâs capital structure in 2005 to 2008 showed changes of its proportion. In 2004 to 2005, firmâs capital structure showed that proportion of 40% debt and 50% capital. In 2005 to 2006, firm had changed its proportion became 20% debt and 80% capital. Its proportion came back to 40% debt and 60% capital in 2007. Capital structure had changed in 2007 due to business expansion in construction and telecommunication field. Firm has issued new shares to make proportion still in 35% debt and 65% capital. In 2008, global market has subprime mortgage crisis issue. It made obstacle for the firmâs project. Most of shares price firmâs coverage fallen down that make the firm must increase more value to coverage. This condition has made negative image for market to the firm. As consequence, firm decided to sell few of its shares that become coverage. This sell action will affect to firmâs capital structure. In this condition, the firm must find another financial source to make its capital structure. Debt will make higher proportion of debt, so that firm has to find a solution to make proportion back to be 40% debt and 60% capital. In 2008, firm make another issued of new shares that make proportion became 35% debt and 60% capital. The conclusion of this analysis is the decision that firm made to sustain its capital structure is right. The optimal proportion of debt and equity is 50% debt and 50% capital.